Studies on Synthesis of Some New Chalcone and Pyrimidines and their Antibacterial Activity - Ketan Mistry; K. R. Desai (E-Journal of Chemistry)
Pyrimidine-2-one derivatives, 2-[2-{1ʹ-(p-nitrophenyl)-6ʹ-(substituted-phenyl)-pyrimidine-2ʹ-one-4ʹ-yl}-hydrazinomethyl]-3-(p-methoxy phenyl)-quina-zoline-4(3H)-one [4a-j] have been synthesised by the condensation of p-nitro phenylurea and various chalcones, 2-(substituted phenylchalconylhydrazinomethyl)-3-(p-methoxyphenyl)-quinazoline-4(3H)-one [3a-j] in the presence of catalytic amount of conc. HCl. And this series of chalcones have been synthesised by the reaction of 2-acetylhydrazinomethyl-3-(substitutedphenyl)-quinazoline-4(3H)-one [2] with different substituted aldehydes in presence of a 2% NaOH solution. These products have been characterized by means of elemental analysis, IR and NMR spectrul studies and tested for antibacterial activities against Staphylococcus aureus, Bacillus subtillis, Escherichia coli and Salmonella typhi.